Impunity and the Marginalization of Women in Nepal: A Socio-cultural Perspective - Yadav, Prabhu (Literary Studies, 2015)
The condition of Nepalese women is as adverse as the plight of Nature which is treated by people for their own vested interest. The thinking of people around the world is different from the aesthetic beauty of women as well as Nature. However, we can't expect a world without women or nature. To conserve the integrity and sovereignty of Nature and women is a big problem today. It is the responsibility of the government to preserve women's dignity in society. A rich and prosperous society can't be positively imagined unless men show respect and regard for the empowerment of women.